WHY DID IRANIAN GIRLS PERFORM BETTER THAN BOYS IN MATHEMATICS? - Ali Reza Kiamanesh (Proceedings of ICMSA, 2005)
Research literature on gender differences in math shows that male advantage inmathematics achievement is a universal phenomenon. One of the mostremarkable results of two international studies, i.e., TIMSS 1999 and TIMSS2003 (Trends in Internatioaal Mathematics and Science Study), for hanianfourth and eighth graders is that boys' math achievement score had a significantdecrease and that of girls a significant improvement. The focus of the presentstudy was on changes in Iranian boys' and girls' math achievement in TIMSS 99and 2003 in grade eight and it sought to identi different predictor variableswhich might have resulted in girls' higher nmttematics achievement.Keywords: Matlematics Achievement; Gender Differences; Math Self-Concept;Attitudes towards lvlath